PENGARUH UMUR PERUSAHAAN, PROFITABILITAS DAN KOMITE AUDIT TERHADAP INTEGRATED REPORTING - ARUM DWI PRAWESTI, DIANAR (Jurnal Akuntansi AKUNESA, 2019)
There are many cases of financial manipulation statements led to the emergence of non-financial reports such as integrated reporting. This study aims to determine the effect?s of company age, profitability and audit committe on integrated reporting. Sample used in this study is the company included in the LQ45 index with the research time 2014-2016. The type of research used is quantitative research with sampling method using purposive sampling technique. Hypothesis testing in this research using multiple regression analysis. The results showed that company age has a significant effect on integrated reporting because the longer the company operates, the greater the information asymmetry that occurs within the company, so the company will disclose information on one of them integrated reporting, profitability and audit committe has no effect on integrated reporting.Keywords: Integrated Reporting, Company age, Profitability and audit committe